Assessing dental surgeons' understanding of bisphosphonates: Implications for patient health in oral surgery - Vilson Rocha Cortez Teles de Alencar; Marcília Ribeiro Paulino; Inês Andrea Luna Martinis de Alencar; Jaime Ribeiro-Filho; Ana Valéria de Oliveira Braz; Edinardo Fagner Ferreira Matias; João Paulo Martins de Lima; Sloana Giesta Lemos Florencio; Henrique Douglas Melo Coutinho; Antônio Marcos Montagner (Saudi Dental Journal)
Objectives: This study aimed to analyze the knowledge of dental surgeons concerning the pharmacological effects of bisphosphonates (BP) and their impact on the health of patients undergoing oral surgery treatment. Materials and methods: A quantitative study was conducted with professionals in the Cariri region of Ceará, Brazil. The data were collected using a semi-structured questionnaire to interview the dental surgeons who met the inclusion criteria. The data were analyzed by Chi-square and Fischer's Exact tests using the SPSS program version 22.0. Results: The results indicated that most interviewed subjects have no experience with the dental treatment of individuals under treatment with bisphosphonates. When a sample of the medication was presented, a significant number of the participants (65.3%) did not recognize the drug. Among those who recognized it, 66.5% did not know how to treat bisphosphonate-using patients in the clinical routine. However, 95.1% of the professionals who recognized the need to discontinue these drugs admitted contacting the prescriber to establish the best dental conduct. Our results also showed that recently graduated professionals better understood the need to stop BP use before invasive treatment, although they did not know the protocol. Conclusion: In conclusion, a better knowledge of the pharmacological effects of BP is crucial for conducting adequate anamnesis, requesting additional tests, and performing medical monitoring, which has a significant impact on the clinical practice of dental surgeons.